Gene expression during activation of Paracoccidioides brasiliensis conidia - Hernandez, O. (2011)
This study focuses on gene expression during crucial biological phenomena of the dimorphic fungal human pathogen Paracoccidioides brasiliensis, the conidia-to-yeast (C-Y) transition and the conidia-to-mycelia (C-M) germination. We studied 10 genes involved in different cellular functions: oxidative stress response (alternative oxidase (AOX), superoxide dismutase (SOD), flavodoxin, conserved hypothetical protein (Y20)); cell metabolism (glyceraldehyde-3-phosphate dehydrogenase (GADPH), cholestenol Delta-isomerase (ChDI), glycine dehydrogenase (GDh)) and heat shock response (Heat shock protein 90 (HSP90)), and cell synthesis and wall structure (glucan synthase-1 (GS-1), α-1,3-glucan synthase (αGS), and mannosyltransferase (MT)). Gene expression was measured during the first 72 h and 96 h of C-Y and C-M, respectively, previously shown to be a fundamental time frame for the consolidation of these cellular processes. The gene expression of AOX, GAPDH, HSP90, MT, αGS, and GDh was significantly increased during the C-Y transition, while SOD, ChDI, GAPDH, MT, GDh, and GS-1 were increased during C-M germination. Additionally, some were highly expressed in each process: AOX, HSP90, and αGS during C-Y; SOD, ChDI, and GS-1 during C-M. Altogether, these data add new information regarding gene expression during the C-Y and C-M processes. Future research will be targeted to further characterize the true relevance of the studied genes during the morphological transition, either during adaptation to the environment or to the infected host.